THE INFLUENCE OF LEADERSHIP, TRAINING AND WORK DISCIPLINE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE ON THE PERFORMANCE OF EMPLOYEES OF THE PEKANBARU CITY BRANCH OF BPJS EMPLOYEES - Iwan Kurniawan; Chablullah Wibisono; Muammar Khaddafi; Indrayani; Muhammad Gita Indrawan (CV. Radja Publika, 2023)
This research was carried out at the BPJS Employment Pekanbaru City Branch Office, over a period of five months from April 2023 to August 2023.The population in this study were employees who worked at the BPJS Employment Office, Pekanbaru City Branch, totaling 124 respondents regardless of strata and specific areas of work.This research uses path analysis to test relationship patterns that reveal the influence of a variable or set of variables on other variables, both direct and indirect influences. So hypothesis one states that the influence of leadership on work motivation is significant. Hypothesis two states that the influence of Leadership on the Performance variable is significant. The third hypothesis states that the influence of training on work motivation is significant. The fourth hypothesis states that the influence of training on performance is significant. The fifth hypothesis states that the influence of Work Discipline on Work Motivation is significant. The sixth hypothesis states that the influence of Work Discipline on the Performance variable is significant. The seventh hypothesis states that the influence of work motivation on performance is significant. The eighth hypothesis states the direct influence of Leadership on Performance, thus it can be stated that Work Motivation can mediate the influence of Leadership on Performance. The ninth hypothesis states the direct influence of training on performance, thus it can be stated that work motivation can mediate the influence of training on performance. The tenth hypothesis states the direct influence of Work Discipline on Performance, thus it can be stated that Work Motivation can mediate the influence of Work Discipline on Performance.